The Impact of Financial Performance on the Technology Sector Stock Price Listed on the Indonesia Stock Exchange in 2021–2023 - Citra Dwinata; Wiwin Indri Astuti; Ario Purdianto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study was conducted to evaluate the extent to which financial performance plays a role in the stock price movements of technology sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. In this study, Return on Assets (ROA), Earning Per Share (EPS), and Debt to Equity Ratio (DER) were used as independent variables, while stock prices were used as tied variables. The research method used is a quantitative approach with the application of multiple linear regression analysis, using the help of SPSS software version 27. Research data was obtained from 22 companies selected through the purposive sampling method, resulting in a total of 66 observational data in a span of three years. The findings of this study reveal that ROA and EPS have a significant impact on stock price changes, showing that solid financial performance is a particular attraction for investors. In contrast, DERs have no real influence on stock prices, which shows that investors in the technology sector tend to pay less attention to debt ratios when considering their investment decisions. This research provides practical implications for companies and investors. Companies are advised to improve operational efficiency to increase ROA and EPS, while investors can use both ratios as indicators in investment decision-making. This research also opens up opportunities for further studies in exploring other external factors that can affect stock price fluctuations in technology companies.